Levels and Trends of Fecundity Hormones in Adolescence - FARKHANDA GHAFOOR, ASMA MUNIR, ATIYA, RABAIL JAVED (Journal of Fatima Jinnah Medical University, 2018)
Objective: To find the trends of fertility hormone profile among teenagers. Study design: Retrospective analytical study. Method: Recorded data in NHRC lab (year 2006- 2011) was statistically analyzed for different fertility hormones including leutinizing hormone (LH), follicular stimulating hormone (FSH), prolactin, testosterone, progesterone and cortisol, in teenager boys and girls (13-19 years). Results: Out of 218 registered cases, 30 were males and 188 were females. An increase in cases of polycystic ovaries (PCO) was seen in 2007, 2010 and 2011. Hirsutism and infertility cases were high in year 2010 and 2011. Conclusion: Disturbances of fecundity hormones can lead to an increase in infertility and obesity in both sexes and diseases as PCO and hirsutism in females. The causes of this increase should be seriously looked into and further elucidated by detailed and large scale study